The Effect of Jakarta Interbank Offered Rate, Stock Transaction Value, Inflation, and Non- Performing Financing on the Stock Price of PT. Bank Syariah Indonesia Tbk - Wulan, Puteri Nawang; Imaningsih, Niniek (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study analyzes the effect of the Jakarta Interbank Offered Rate (JIBOR), stock transaction value, inflation, and Non-Performing Financing (NPF) on the stock price of PT Bank Syariah Indonesia Tbk (BSI). Using a quantitative approach with multiple linear regression, the research covers the period from the first quarter of 2021 to the fourth quarter of 2024 with secondary data obtained from the IDX, Bank Indonesia, OJK, and BPS. The results show that stock transaction value has a significant positive effect on BSIâ€™s stock price, while inflation has a significant negative effect. In contrast, JIBOR and NPF do not significantly influence stock price movements. The adjusted RÂ² value of 0.8369 indicates that 83.69% of stock price variation can be explained by the independent variables. These findings suggest that market liquidity and inflation are the main determinants of Islamic stock price performance, while conventional monetary indicators and internal risk factors are less influential. This study contributes to the literature on the Islamic capital market and provides practical insights for investors, regulators, and bank management in formulating investment and risk management strategies